Elevated cytokine levels in tears and saliva of patients with primary Sjögren’s syndrome correlate with clinical ocular and oral manifestations - Chen, Xiangjun; Aqrawi, Lara A.; Utheim, Tor Paaske; Tashbayev, Behzod; Utheim, Øygunn Aass; Reppe, Sjur; Hove, Lene Hystad; Herlofson, Bente Brokstad; Singh, Preet Bano; Palm, Øyvind; Galtung, Hilde Kanli; Jensen, Janicke Cecilie Liaaen (Scientific reports, 2019)
Investigating cytokines in tear fluid and saliva may offer valuable information for understanding the pathogenesis of primary Sjögren’s syndrome (pSS). Cytokine profiles in both tear fluid and saliva of pSS patients, non-Sjögren’s syndrome (non-SS) subjects with sicca symptoms, and healthy controls without sicca complaints were analysed. Furthermore, relationships associating the severity of clinical ocular and oral manifestations with the upregulated cytokines were assessed. In tear fluid, pSS patients showed elevated levels of IL-1ra, IL-2, IL-4, IL-8, IL-12p70, IL-17A, IFN-γ, IP-10, MIP-1b, and Rantes compared to non-SS subjects and healthy controls. The increased cytokine levels (except IP-10) correlated significantly with reduced tear production, less stable tear film, and greater ocular surface damage. In saliva, pSS patients had a higher IP-10 level, which correlated with higher candida score; and an elevated MIP-1a level, which correlated significantly with lower unstimulated and stimulated whole saliva secretion rates. The upregulated cytokines identified in tear fluid and saliva of pSS patients show a clear interplay between innate and adaptive immune responses that may contribute to disease pathogenesis. The increase of IP-10 and MIP in both tears and saliva further emphasises the essential role of macrophages and innate immunity in pSS.